Gulf hydrogen horizons: why are Gulf oil and gas producers so keen on hydrogen? - Koch, Natalie (IASS discussion papers, 2022)
Autor: Koch, Natalie; Genre: Forschungspapier; Final veröffentlicht: 2022-11; Open Access; Titel: Gulf Hydrogen Horizons. Why are Gulf oil and gas producers so keen on hydrogen?